The (im)possibilities of teaching-learning freedom - Becker, Anne (South African Journal of Higher Education, 2016)
Twenty years after a free and democratic South Africa was constituted, it seems as if South Africans are still in limbo. In this article I explore the essence of freedom as conceptualised by Arendt (1958, 1966; 1900; 2006) and the (im)possibilities of teaching-learning freedom towards continual new beginnings. Freedom and new beginnings are actualised when humans speak and act in equal difference. The possibilities of teaching-learning freedom rely on the acknowledgement of both the burden and the power of freedom and in unexpected acts of compassion and forgiveness in the teacher:child relationship. Using a phenomenological approach I explore qualitative data from the research project Human Rights Literacy: A quest for meaning (Roux, 2012) to explore the (im)possibilities of teaching-learning freedom.